An Italian Adaptation of the Burnout Assessment Tool-Core Symptoms (BAT-C) for Students - Luciano Romano; Giacomo Angelini; Piermarco Consiglio; Caterina Fiorilli (MDPI AG, 2022)
Burnout is psychological, physical, and emotional suffering that may affect students with low or inadequate resources to face stressful events at school. Although the existing instruments are used worldwide to assess school burnout risk, they show several flaws and mainly focus on the emotional facets of the syndrome. No previous studies have developed a multi-component tool to reveal students' burnout by simultaneously analyzing cognitive, behavioral, and emotional problems. The central core of the current study is to adapt the Burnout Assessment Tool-Core symptoms (BAT-C; Schaufeli et al., 2020), comprising four subscales, exhaustion, mental distance, cognitive impairment, and emotional impairment, for a sample of Italian students. The factor structure, the reliability, and the validity of the scale are investigated. The participants are 745 middle school students (male, 52.2%; aged 9-13, M = 11.84, and SD = 1.21). Confirmatory factor analyses confirmed the best fit of the second-order model (four first-order factors and one second-order factor). Specifically, four factors were loaded onto a main high-order factor, which constitutes the BAT-C. Our findings support the Italian adaptation of the BAT-C for students' samples as a valid instrument for measuring the core symptoms of school burnout.